Exploratory Study of Functional Movement in Rope Climbing - Chi-sun Choi; Won-je Cho; Kyoung-bae Kim (Korea Institute of Sport Science, 2022)
PURPOSE This study aimed to explore the functional movement in rope climbing. METHODS The rope climbing experiment included 16 healthy young male participants, and the methods of hand, cross-leg, and foot-hooking climbing were employed. The muscle activity and joint range of motion were measured and analyzed using EMG (Electromyography) and IMU (Inertial Measurement Unit) sensors. One-way analysis of variance was conducted (α<.05). RESULTS The activity of the forearm and biceps muscle was lower in cross-leg and foot-hooking climbing compared to hand climbing (p<.01), and the rectus femoris muscle activity in cross-leg climbing was smaller than that in hand climbing (p<.05). Furthermore, the adductor muscle activity in cross-leg climbing was higher than that of other types (p<.01). The range of motion for the elbow and shoulder flexion was smaller in hand climbing than in other types (p<.05); furthermore, the range of motion in the pelvis, thigh, and knee joint was the smallest in cross-leg climbing (p<.05). CONCLUSIONS Because the pulling muscles such as the forearm, biceps, pectoralis major, and latissimus dorsi play an important role in the entire climbing motion, it is necessary to train the upper-body pulling-muscle group along with strengthening the core and lower body muscles.